Flexible collective bargaining agreements: Still a moderating effect on works council behaviour? - Tobias Brändle (Institut für Angewandte Wirtschaftsforschung (IAW), 2013)
We analyse the interaction between different labour market institutions in Germany, a country with a long tradition of strong bargaining partners. A number of studies have established that industry-level bargaining exerts a moderating role on firm-level co-determination: works councils generate rather than redistribute rents in plants covered by collective bargaining agreements. This work analyses whether these findings still hold, given recent developments in the German system of industrial relations towards more bargaining decentralisation, such as opening clauses or company-level pacts for employment. In addition, we provide evidence pertaining to whether labour market reforms targeted at one institution (a push of collective bargaining agreements towards more flexibility) are counteracted by altering the effects of other, unaffected institutions (the rent-seeking behaviour of works councils). Analysing institutional changes and augmenting a theoretical model provides hypotheses, which are then tested using empirical analysis of representative German plant level data. We find that the existence of flexibility provisions in collective bargaining agreements do not drive works council behaviour towards rent-seeking. Regarding rent-generation, we find an amplifying effect: works council existence is associated with higher productivity in plants covered by industry-level contracts. These findings, however, depend on the level of collective bargaining: they do not hold in plants covered by firm-level contracts.
Keywords: J53; J31; 330; works councils; collective bargaining; employment pacts; opening clauses; wages; productivity